2019
DOI: 10.4236/ce.2019.1011179
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Relationship on Science Achievement amongst National Secondary School Students

Abstract: This study has aimed to identify the relationship of self-efficacy in science with academic achievement amongst national secondary school students in the Rompin district. This study is a quantitative research using the survey method through a questionnaire. A total of 191 students from 4 schools in the Rompin were involved in this study. The data were analysed using descriptive and inferential statistics methods. This study found that practical work was the highest contributing factor to student self-efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
4
9
1
2
Order By: Relevance
“…Meanwhile, students with low self-efficacy tend to not interested to involve in the learning process and consequently, they will have shallow knowledge and low academic achievement. Different results obtained from the study by Jamil & Mahmud (2019), where they found selfefficacy has a small correlation with science achievement (r = 0.124, p > 0.05). Furthermore, female students have higher self-efficacy (M = 3.49, SD = 0.363) compared to male students (M = 3.28, SD -0.384).…”
Section: Literature Reviewcontrasting
confidence: 71%
“…Meanwhile, students with low self-efficacy tend to not interested to involve in the learning process and consequently, they will have shallow knowledge and low academic achievement. Different results obtained from the study by Jamil & Mahmud (2019), where they found selfefficacy has a small correlation with science achievement (r = 0.124, p > 0.05). Furthermore, female students have higher self-efficacy (M = 3.49, SD = 0.363) compared to male students (M = 3.28, SD -0.384).…”
Section: Literature Reviewcontrasting
confidence: 71%
“…The indicators of self-efficacy, included generality, magnitude, and strength (Bandura, 1994) if, in good or adequate condition, it can increase achievement motivation reflected in the desire to be the best, responsibility, consider the risks, feedback, creative-innovative, and task completion time (McClelland, 1976). The studies carried out by Alhadabi and Karpinski (2019), Jamil and Mahmud (2019), Benawa (2018), and Liu and Cheng (2018) also reveal that self-efficacy affects achievement motivation. Based on argues and studies above, the fifth hypothesis in this study is: H5: Self-efficacy had a direct effect on achievement motivation.…”
Section: Self-efficacy and Achievement Motivationmentioning
confidence: 93%
“…The indicators of personality, such as extraversion, agreeableness, conscientiousness, openness to experience, and neuroticism (Costa & McCrae, 1992) if in an adequate condition potentially supporting self-efficacy manifested generality, magnitude, and strength (Bandura, 1994) and then impacted achievement motivation reflected in the desire to be the best, responsibility, consider the risks, feedback, creative-innovative, and task completion time (McClelland, 1976). The studies carried out by Abood et al (2020), and Murugesan and Jayavelu (2017) concluded that personality affects self-efficacy, while the studies conducted by Alhadabi and Karpinski (2019), Jamil and Mahmud (2019), Benawa (2018), and Liu and Cheng (2018) reveal that self-efficacy influences achievement motivation. Based on argues and studies above, the ninth hypothesis in this study is: H9: Personality had an indirect effect on achievement motivation mediating by self-efficacy.…”
Section: Personality On Achievement Motivation Mediating By Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…A few Asian researchers have shown great interest in using science learning selfefficacy (SLSE) [24][25][26] in self-efficacy studies. This scale measures science self-efficacy with the presence of five dimensions, comprising conceptual understanding, higher order thinking skills, practical work, daily life applications, and science communication.…”
Section: Science Self-efficacy Scalementioning
confidence: 99%